The Use of Online Authentic Reading Materials In Online Reading Class - Fifi Nur Ulwiyah (Department of English Language Education, UIN Sunan Ampel Surabaya, 2021)
Abstract. Education in Indonesia, as the large-scale power of the has to be compelled the continuity of teaching activities during the COVID-19 pandemic online learning. It inspires teachers to choose a suitable material to fulfill students’ needs and interests in teaching language. The appropriateness and well chosen authentic materials used by teachers in a context of reading have to cover meaningful content in which those are relevant. Thus, this study attempts to investigate those authenticity used as well as teachers’ challenges in implementing online authentic reading materials in online reading class of higher education. The study is a qualitative. The subjects are three EFL teachers of higher education that teach General English and English for Specific Purposes freshmen for two semesters. The data collection techniques are observation and interview. In analyzing the data, this study uses Ary et al. (2010) theory: familiarizing and organizing; coding and reduction; interpreting and representing. The findings revealed that authenticity is considered as the pivotal thing since, in this case, English is taught as foreign language. The authentic materials can be said its prevalence by measuring each authenticity based on three areas including SLA (Second Language Acquisition), language pedagogy and ICT (Information and Communication Technology). It could establish the applied authenticity to the language learning design materials, especially learning English language. Moreover, The challenge was about the materials, students’ interests, classroom activities and classroom interaction occurred among teachers and the students.